Higher aggrecan 1-F21 epitope concentration in synovial fluid early after anterior cruciate ligament injury is associated with worse knee cartilage quality assessed by gadolinium enhanced magnetic resonance imaging 20 years later - Paul Neuman (BMC Musculoskeletal Disorders, 2020)
Abstract Background To investigate if cartilage related biomarkers in synovial fluid are associated with knee cartilage status 20 years after an anterior cruciate ligament (ACL) injury. Methods We studied 25 patients with a complete ACL rupture without subsequent ACL reconstruction or radiographic knee OA. All had a delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) 20 years after the ACL injury, using the T1 transverse relaxation time in the presence of gadolinium (T1Gd) which estimates the concentration of glycosaminoglycans in hyaline cartilage. Synovial fluid samples were aspirated acutely (between 0 and 18 days) and during 1 to 5 follow up visits between 0.5 and 7.5 years after injury. We quantified synovial fluid concentrations of aggrecan (epitopes 1-F21 and ARGS), cartilage oligomeric matrix protein, matrix metalloproteinase-3 and tissue inhibitor of metalloproteinase-1 by immunoassays, and sulfated glycosaminoglycans by Alcian blue precipitation. Western blot was used for qualitative analyses of aggrecan fragments in synovial fluid and cartilage samples. Results Western blot indicated that the 1-F21 epitope was located within the chondroitin sulfate 2 region of aggrecan. Linear regression analyses (adjusted for age, sex, body mass index and time between injury and sampling) showed that acute higher synovial fluid 1-F21-aggrecan concentrations were associated with shorter T1Gd values 20 years after injury, i.e. inferior cartilage quality (standardized effects between − 0.67 and − 1.0). No other statistically significant association was found between molecular biomarkers and T1Gd values. Conclusion Higher acute synovial fluid 1-F21-aggrecan concentrations in ACL injured patients, who managed to cope without ACL reconstruction and were without radiographic knee OA, were associated with inferior knee cartilage quality assessed by dGEMRIC 20 years after injury.